ASSESSING THE ACCURACY OF FIB-4 SCORES TO POINT SHEAR WAVE ELASTOGRAPHY IN MONITORING DIFFERENT STAGES OF FIBROSIS IN NON-ALCOHOLIC LIVER DISEASE. - Rasul, Shahla Mohammed Saeed (Journal of Sulaimani Medical College, 2025)
Background Non-alcoholic liver disease (NAFLD) assessment is done by measuring biochemical parameters from blood samples. However, non-invasive methods have gained significance lately. Biochemical parameters and staging of fibrosis-associated NAFLD based on the levels of biomarkers have been established procedures in the field. So, the utilization of non-invasive methods as a comparable means for fibrosis staging in NAFLD has yet to be established. Objectives To compare the diagnostic performance of serum markers to point shear wave elastography for classifying fibrosis in NAFLD and its staging. Materials and Methods Data were collected by laboratory tests and point shear wave elastography. A comparison of FIB-4 indexes scores and point shear wave elastography for the staging of fibrosis in NAFLD was made based on crosstabulation of the quantitative data obtained. Results A positive and significant correlation between FIB4 and age, ALT, AST, RBS, AST/ ALT, AST/ UL AST, APRI, AST/ Platelet count, and point shear wave elastography (PSWE). The correlation was negative and nonsignificant between FIB4 and Weight, Height, BMI, UL AST, TSB, and Platelet count. Conclusion The study observed a positive correlation between FIB-4 and PSWE. Thus, the present study proposes the use of PSWE as a non-invasive diagnostic tool in the staging of fibrosis in NAFLD for patients with an intermediate FIB-4 score.
Keywords: Fibrosis; 2D SWE; liver cirrhosis; NAFLD; serum markers; elastography; FIB4 scoring,point shear wave elastography; APRI